Spatial relationships between the standing vegetation and the soil seed bank in a fire-prone encroached dehesa in Central Spain - Torres, Ivan; Cespedes, Blanca; Perez, Beatriz; Moreno, Jose M. (PLANT ECOLOGY, 2013)
Postfire vegetation regeneration in many fire-prone ecosystems is soil seed bank dependent. Although vegetation and seed bank may be spatially structured, the role of prefire vegetation patterns and fire in determining postfire vegetation patterns is poorly known. Here, we investigated the spatial patterning of species abundance and richness in the vegetation and seed bank of a Mediterranean encroached dehesa in Central Spain. The seed bank was studied with and without a heat shock simulating a spatially homogeneous fire. Semivariograms and cross-semivariograms showed that species richness in the vegetation was aggregated in patches, mainly of herbs, with highest values corresponding to high herb cover and low tree cover. Species richness in the seed bank was also structured in patches, but the spatial pattern was weak. Seedling density of germinates in the seed bank also showed weak spatial pattern. Heating increased overall germination and species richness, and the intensity of the spatial pattern of species richness, particularly of herbaceous species. However, seed bank density patterns disappeared after heat shock because of increased germination of shrubs without spatial pattern. Our results document that the spatial structure of plant richness in the vegetation may persist after fire due to the spatial patterns of herbaceous species in the seed bank, and that postfire species richness patterns can arise independently of fire intensity patterns. However, the spatial structure of the vegetation after fire can be altered by the feedback between shrub encroachment and an eventual fire because of the ubiquitous germination of shrubs.
The following values have no corresponding Zotero field: pub-location: VAN GODEWIJCKSTRAAT 30, 3311 GZ DORDRECHT, NETHERLANDS publisher: SPRINGER
Keywords: Land abandonment; Land-use change; Seeder; Semivariogram; Species richness

Spatial relationships between the standing vegetation and the soil seed bank in a fire-prone encroached dehesa in Central Spain - Torres, Ivan; Cespedes, Blanca; Perez, Beatriz; Moreno, Jose M (PLANT ECOLOGY, 2013)
Postfire vegetation regeneration in many fire-prone ecosystems is soil seed bank dependent. Although vegetation and seed bank may be spatially structured, the role of prefire vegetation patterns and fire in determining postfire vegetation patterns is poorly known. Here, we investigated the spatial patterning of species abundance and richness in the vegetation and seed bank of a Mediterranean encroached dehesa in Central Spain. The seed bank was studied with and without a heat shock simulating a spatially homogeneous fire. Semivariograms and cross-semivariograms showed that species richness in the vegetation was aggregated in patches, mainly of herbs, with highest values corresponding to high herb cover and low tree cover. Species richness in the seed bank was also structured in patches, but the spatial pattern was weak. Seedling density of germinates in the seed bank also showed weak spatial pattern. Heating increased overall germination and species richness, and the intensity of the spatial pattern of species richness, particularly of herbaceous species. However, seed bank density patterns disappeared after heat shock because of increased germination of shrubs without spatial pattern. Our results document that the spatial structure of plant richness in the vegetation may persist after fire due to the spatial patterns of herbaceous species in the seed bank, and that postfire species richness patterns can arise independently of fire intensity patterns. However, the spatial structure of the vegetation after fire can be altered by the feedback between shrub encroachment and an eventual fire because of the ubiquitous germination of shrubs.
Keywords: Land abandonment; Land-use change; Seeder; Semivariogram; Species richness